2022
DOI: 10.3390/ijerph19159199
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Psychological Interventions for Reducing Stress, Anxiety, and Depression among University Students during the COVID-19 Pandemic

Abstract: (1) Background: The aim of this study is to investigate the effects of internet-based intervention programs for reducing stress, anxiety, and depression among university students during the COVID-19 pandemic by conducting a meta-analysis. (2) Methods: Searches were conducted in the following databases: MEDLINE, EbscoHost Academic Search Ultimate, and PsycArticles, using a combination of “Covid-19 AND ‘Randomized Controlled Trial’ AND students”, as well as a combination of the following search terms: “internet”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…The present study has revealed that university undergraduate students' total perceived academic stress levels were higher after the first wave than those of after the second wave of COVID-19 (effect size was week, Cohen's d = 0.49), what is in agreement with the data found by Rogowska et al (2021b), where the differences between waves in perceived stress "were significant, with moderate effect size, χ 2 (2) = 152.69, p < 0.001, Cramer's V = 0.28)" (Rogowska et al, 2021b, p. 6) or with the data found by Panteli et al (2021), where effect size was small (Cohen's d = 0.37). The present research data may be explained by the data of meta-analysis (Malinauskas, Malinauskiene, 2022), which emphasises that during the beginning of COVID-19 pandemic, undergraduates' perceived stress have only increased. "Students experiencing worsened depressive symptoms, diminished sleep quality, increased anxiety, social disconnectedness, an absence of peer support, loneliness, gloom, and outrage" (Malinauskas, Malinauskiene, 2022: 2).…”
Section: Discussionmentioning
confidence: 83%
“…The present study has revealed that university undergraduate students' total perceived academic stress levels were higher after the first wave than those of after the second wave of COVID-19 (effect size was week, Cohen's d = 0.49), what is in agreement with the data found by Rogowska et al (2021b), where the differences between waves in perceived stress "were significant, with moderate effect size, χ 2 (2) = 152.69, p < 0.001, Cramer's V = 0.28)" (Rogowska et al, 2021b, p. 6) or with the data found by Panteli et al (2021), where effect size was small (Cohen's d = 0.37). The present research data may be explained by the data of meta-analysis (Malinauskas, Malinauskiene, 2022), which emphasises that during the beginning of COVID-19 pandemic, undergraduates' perceived stress have only increased. "Students experiencing worsened depressive symptoms, diminished sleep quality, increased anxiety, social disconnectedness, an absence of peer support, loneliness, gloom, and outrage" (Malinauskas, Malinauskiene, 2022: 2).…”
Section: Discussionmentioning
confidence: 83%
“…The majority of the online interventions were effective in promoting well-being of higher education students during the pandemic based on evidence from randomized clinical trials, quasiexperimental studies, and cohort or case-control studies (da Silva et al, 2022; Malinauskas & Malinauskiene, 2022; Riboldi et al, 2022). Within this, particularly online group mindfulness techniques and web-based cognitive behavioral therapies (da Silva et al, 2022), multicomponent online positive psychology interventions (Malinauskas & Malinauskiene, 2022), and individually catered cognitive behavioral therapies, dialectical behavior therapies, and mind-body practice techniques (Riboldi et al, 2022) emerged as being effective.…”
Section: Resultsmentioning
confidence: 99%
“…High psychological stress has been linked to anxiety and depression [ 25 , 26 ]; hence, evaluating it in patients with clinical anxiety is relevant for monitoring its progression. Stress is also a risk factor for mental health problems and can be managed through psychological interventions [ 27 , 28 ]. In addition, studies evaluating other symptoms in patients with mental health problems that came up in the search were included if they involved intrusive thoughts or suicidal thoughts and suicidal ideation.…”
Section: Methodsmentioning
confidence: 99%